Optical genome mapping for detection of chromosomal aberrations in prenatal diagnosis - Qinxin Zhang; Yan Wang; Yiyun Xu; Ran Zhou; Mingtao Huang; Fengchang Qiao; Lulu Meng; An Liu; Jing Zhou; Li Li; Xiuqing Ji; Zhengfeng Xu; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Chromosomal aberrations are the most important etiological factors for birth defects. Optical genome mapping is a novel cytogenetic tool for detecting a broad range of chromosomal aberrations in a single assay, but relevant clinical feasibility studies of optical genome mapping in prenatal diagnosis are limited. Material and methods We retrospectively performed optical genome mapping analysis of amniotic fluid samples from 34 fetuses with various clinical indications and chromosomal aberrations detected through standard‐of‐care technologies, including karyotyping, fluorescence in situ hybridization, and/or chromosomal microarray analysis. Results In total, we analyzed 46 chromosomal aberrations from 34 amniotic fluid samples, including 5 aneuploidies, 10 large copy number variations, 27 microdeletions/microduplications, 2 translocations, 1 isochromosome, and 1 region of homozygosity. Overall, 45 chromosomal aberrations could be confirmed by our customized analysis strategy. Optical genome mapping reached 97.8% concordant clinical diagnosis with standard‐of‐care methods for all chromosomal aberrations in a blinded fashion. Compared with the widely used chromosomal microarray analysis, optical genome mapping additionally determined the relative orientation and position of repetitive segments for seven cases with duplications or triplications. The additional information provided by optical genome mapping will be conducive to characterizing complex chromosomal rearrangements and allowing us to propose mechanisms to explain rearrangements and predict the genetic recurrence risk. Conclusions Our study highlights that optical genome mapping can provide comprehensive and accurate information on chromosomal aberrations in a single test, suggesting that optical genome mapping has the potential to become a promising cytogenetic tool for prenatal diagnosis.